2016
DOI: 10.1021/acs.jpca.6b06967
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Biexponential Dynamics of Ring-Opening in 7-Dehydrocholesterol

Abstract: Our prior discovery of a novel biexponential photochemical ring-opening in 7-dehydrocholesterol (DHC) to previtamin D3 [ Tang J. Chem. Phys. 2011 , 134 , 104503 ] is further explored with ultrafast transient absorption spectroscopy, and the results are compared with recently reported high-level theoretical calculations. Three types of experiments are reported. First, variation of the excitation wavelength from 297 to 266 nm leaves the excited state dynamics unaffected. The biexponential decay of the excited st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 40 publications
(101 reference statements)
0
13
1
Order By: Relevance
“…35−37 Hence, the dynamics observed should be associated with a relatively structurally uniform ensemble of reactants. Therefore, do the two time scales observed reflect the initial relaxation of the excited reactant, S 1 * → S 1 , followed by electrocyclization, spectral dynamics associated with an intrinsically biexponential/ nonexponential process, 6,7 or rather branching between distinct relaxation pathways, including a competing funnel to the ground state or the formation of other photoproducts (e.g., Figure 1a)? Motivated in part by recent successful applications of threepulse "pump−repump−probe" (PRP) and "pump−dump− probe" spectroscopies to interrogate and manipulate photoinduced dynamics in light-activated materials, 10,38−41 biomolecules, 6,42−44 and charge-transfer events, 45−47 we have developed PRP transient photochemical hole burning, generalized schematically in Figure 1c, to unravel photochemical pathway branching for systems like OTP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35−37 Hence, the dynamics observed should be associated with a relatively structurally uniform ensemble of reactants. Therefore, do the two time scales observed reflect the initial relaxation of the excited reactant, S 1 * → S 1 , followed by electrocyclization, spectral dynamics associated with an intrinsically biexponential/ nonexponential process, 6,7 or rather branching between distinct relaxation pathways, including a competing funnel to the ground state or the formation of other photoproducts (e.g., Figure 1a)? Motivated in part by recent successful applications of threepulse "pump−repump−probe" (PRP) and "pump−dump− probe" spectroscopies to interrogate and manipulate photoinduced dynamics in light-activated materials, 10,38−41 biomolecules, 6,42−44 and charge-transfer events, 45−47 we have developed PRP transient photochemical hole burning, generalized schematically in Figure 1c, to unravel photochemical pathway branching for systems like OTP.…”
mentioning
confidence: 99%
“…10,41 Similarly, Smith et al observed no repumpinduced changes in the ring-opening efficiency of the 7dehydrocholesterol. 6 In contrast, the 340 nm repump is resonant with both species, but the PRP signal is dominated by the repump's action on the photoproduct, as the efficiency of depleting the DHT population with the 340 nm repump pulse maximizes by time scales on which the photochemical formation of DHT has concluded (based on comparison with TAS data). The slight signal decay on the 10s of ps time scale reflects that vibrational cooling impacts (decreases) the efficiency for photochemical depletion of the photoproduct and is consistent with observations from Figures 2b and 3b.…”
mentioning
confidence: 99%
“…Pre itself plays the central role, as it reacts to four distinct main Vita photo isomers (DPI) Pro, Lumi, and Tachy and toxisterols (Toxi). While the provitamin D ringopening and its analogous reaction in cyclohexadiene has been studied extensively, both theoretically [17][18][19][20] and experimentally, 18,[21][22][23][24][25][26] little research has been done to assess the influence of tachysterol on photochemical vitamin D production. In particular, its excited state dynamics has neither been investigated by experiments nor by simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Photoisomerizations underlie a variety of biological phenomena and applications, including the retinal photoresponse that drives vision, the photochemistry of provitamin D, , and bilirubin detoxification through blue-light therapy. Photoisomerization also underlies the responses of molecular photoswitches that can be used to modulate material properties, , as exemplified by molecular photochromism and memory, , light-activated motors and mechanical responses, , and rapidly photoswitchable molecular conductivity and electronics. , Furthermore, photoisomerizations (specifically, photocyclizations) have significant value for preparatory carbon–carbon bond formation and are particularly useful where harsh reagents may damage reactive functional groups. In all of these cases, isomerization occurs in one of the many steps through which photoexcited molecules deactivate energetically. The nature of isomerization products and the efficiency with which they are formed is governed by the shapes and interactions between potential-energy surfaces of two or more molecular electronic states. There has been great interest in using multiphoton inputs in order to open new photoreaction channels along these surfaces or to optimize reaction efficiencies for generating a desired photoisomerization product. Herein, we illustrate how multiphotonic input, selectively chosen, opens a new photoreaction channel for a simple photocyclizing reactant by taking advantage of state-dependent correlations between high-lying excited electronic states.…”
mentioning
confidence: 99%
“…P hotoisomerizations underlie a variety of biological phenomena and applications, including the retinal photoresponse that drives vision, 1−4 the photochemistry of provitamin D, 5,6 and bilirubin detoxification through bluelight therapy. 7−9 Photoisomerization also underlies the responses of molecular photoswitches that can be used to modulate material properties, 10,11 as exemplified by molecular photochromism and memory, 12,13 light-activated motors and mechanical responses, 11,14−16 and rapidly photoswitchable molecular conductivity and electronics.…”
mentioning
confidence: 99%